Detecting insomnia in patients with low back pain: accuracy of four self-report sleep measures - Alsaadi, Saad Mohammed; McAuley, James H.; Hush, Julia M.; Bartlett, Delwyn J.; Henschke, Nicholas; Grunstein, Ronald R.; Maher, Chris G. (BMC musculoskeletal disorders, 2013)
Although insomnia is common in patients with low back pain (LBP), it is unknown whether commonly used self-report sleep measures are sufficiently accurate to screen for insomnia in the LBP population. This study investigated the discriminatory properties of the Pittsburgh Sleep Quality Index (Pittsburgh questionnaire), Insomnia Severity Index (Insomnia index), Epworth Sleepiness Scale (Epworth scale) and the sleep item of the Roland and Morris Disability Questionnaire (Roland item) to detect insomnia in patients with LBP by comparing their accuracy to detect insomnia to a sleep diary. The study also aimed to determine the clinical optimal cut-off scores of the questionnaires to detect insomnia in the LBP population.
Gesehen am 12.05.2021